Confucian Liberalism : Mou Zongsan and Hegelian Liberalism - Tseng, Roy (SUNY series in Chinese Philosophy and Culture, 2023)
Does Confucianism conflict with liberalism? Confucian Liberalism sheds new light on this long-standing debate entwined with the discourse of Chinese modernity. Focusing on the legacy of Mou Zongsan, the book significantly recasts the moral character and political ideal of Confucianism, accompanied by a Hegelian retreatment of the multiple facets of Western modernity and its core values, such as individuality, self-realization, democracy, civilized society, citizenship, public good, freedom, and human rights. The book offers a culturally sensitive way of reevaluating liberal language and forges a reconciliation between the two extremes of anti-Confucian liberalism and anti-liberal Confucianism. The result--Confucian liberalism--is akin to civil liberalism, in that it rests the form of liberal democracy on the content of "Confucian democratic civility." It is also comparable to perfectionist liberalism, endorsing a nondominant concept of the common good surrounded by a set of "Confucian governing and civic virtues."